Concise enantioselective synthesis of (+)-sertraline and (-)-CP-52002 using proline catalysis - Kalshetti, Rupali G.; Venkataramasubramanian, V.; Kamble, Sanjay P.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A short enantioselective synthesis of (+)-sertraline and its C-4 epimer (-)-CP-52002 with an overall yield of 30%, respectively, as its hydrochloride has been described. The key steps are the proline catalyzed Mannich reaction of acetaldehyde and acid catalyzed intramolecular Friedel-Crafts' alkylation reaction of olefin proceeding with high optical purities. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Indatraline; Mannich reaction; Proline catalysis; Sertraline; Tametraline